(3JMaI GdehOhO HCMcGe GdehdhOs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdYXje CeG HYO , aEf Gddg SHMGfg hJYGdi fhY CMcGeg Ydi GdEfSGf ef Mjf NQhLg Edi gPg GdOGQ s
(3BNQgG (B:s
(3Ke jbhd jG Cgd GdLfI NdhO hdG ehJ hjG Cgd GdfGQ NdhO hdG ehJ agPG BNQ CMhGd gPg GdfWaI ai ejOGf GdEfSGf Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs